Itajaí, Santa Catarina – Azorean ancestry and spinocerebellar ataxia type 3 - Hélio A. G. Teive; Adriana Moro; Walter O. Arruda; Salmo Raskin; Gladys M. G. Teive; Norberto Dallabrida; Renato P. Munhoz (Arquivos de Neuro-Psiquiatria)
ABSTRACT The authors present a historical review of spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3/MJD), the most common form of spinocerebellar ataxia in Brazil, and consider the high frequency of cases in families from Itajaí, a city on the coast of the state of Santa Catarina with a large population of Portuguese/Azorean descent.